2011
DOI: 10.1590/s1516-05722011000100002
|View full text |Cite
|
Sign up to set email alerts
|

Rendimento, composição química e atividade antilisterial de óleos essenciais de espécies de Cymbopogon

Abstract: RESUMO:Objetivou-se determinar o rendimento, a composição química e avaliar a atividade antilisterial dos óleos essenciais de Cymbopogon citratus (DC.) Stapf. (capim-limão) e Cymbopogon nardus (L.) Rendle (capim-citronela), puros e em combinação. A obtenção dos óleos essenciais foi realizada a partir de folhas frescas, empregando-se a técnica de hidrodestilação e utilizandose aparelho de Clevenger modificado. Os rendimentos foram calculados a partir da massa obtida na extração e da umidade do material vegetal.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
19
0
21

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(42 citation statements)
references
References 31 publications
2
19
0
21
Order By: Relevance
“…The main component of the essential oil of lemongrass is citral, and antifungal activity is a prominent property Averages followed by the same letter in a column for each type of oil, do not differ by the Tukey test at 5% significance; ** Significant at 1% probability by t-test of this oil (SILVA et al, 2009). Oliveira et al (2011) relate the antimicrobial potential of lemongrass oil to its major components, the monoterpene aldehydes, neral and geranial.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The main component of the essential oil of lemongrass is citral, and antifungal activity is a prominent property Averages followed by the same letter in a column for each type of oil, do not differ by the Tukey test at 5% significance; ** Significant at 1% probability by t-test of this oil (SILVA et al, 2009). Oliveira et al (2011) relate the antimicrobial potential of lemongrass oil to its major components, the monoterpene aldehydes, neral and geranial.…”
Section: Resultsmentioning
confidence: 99%
“…Medice et al (2007), using the essential oil of citronella, observed inhibition of spore germination of the fungus Phakopsora pachyrhizi, the causal agent of Asian soybean rust. Oliveira et al (2011), evaluating the chemical composition of the essential oil of citronella, highlighted as major compounds the aldehyde citronellal and the alcohols geraniol and citronellol, all compounds responsible for the antimicrobial activity of the oil.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Dessa forma, é crescente a procura por plantas medicinais e aromáticas em diversos países, devido à tendência dos consumidores em utilizarem, preferencialmente, produtos farmacêuticos ou alimentícios de origem natural. Assim, tecnologias naturais de conservação vêm se tornando cada vez mais importantes em indústrias de alimentos e os óleos essenciais constituem alternativas à obtenção de produtos microbiologicamente seguros 3 . As plantas medicinais aromáticas apresentam em sua composição óleos essenciais.…”
Section: Introductionunclassified